My brain : an exciting way to learn about your body. - Hewitt, Sally (Laguna Hills, CA : QEB pub, 2008)
"An introduction to the brain and its many functions within the human body, including how it helps us breathe, move, sense, learn, and remember"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Brain --Juvenile literature